Ein Leben im Gegenglück des Geistes - Moisy, Sigrid von,Nodia, Nino,Ikas, Wolfgang-Valentin,Friedrich, Heinz,Saur, Klaus Gerhard (Bayerische Staatsbibliothek, 2005)
Exhibition catalog on Friedrich's life and work, including a section on his 30 years as head of the Deutscher Taschenbuch Verlag.
Keywords: Ausstellungskatalog; Biografie; Festschrift; Friedrich; Heinz <1922-2004>; Friedrich; Heinz; Geschichte; Book industries and trade; Publishers and publishing; Literatur; Deutsch